In vivo scanning laser fundus and high-resolution OCT imaging of retinal ganglion cell injury in a non-human primate model with an activatable fluorescent-labeled TAT peptide probe. - Xudong Qiu; Seth T Gammon; Carol Rasmussen; Federica Pisaneschi; Charlene B Y Kim; James Ver Hoeve; Steven W Millward; Edward M Barnett; T Michael Nork; Paul L Kaufman; David Piwnica-Worms (PLoS ONE)
The optical imaging agent TcapQ488 has enabled imaging of retinal ganglion cell (RGC) injury in vivo in rodents and has potential as an effective diagnostic probe for early detection and intervention monitoring in glaucoma patients. In the present study, we investigated TcapQ488 in non-human primates (NHPs) to identify labeling efficacy and early signals of injured RGC, to determine species-dependent changes in RGC probe uptake and clearance, and to determine dose-limiting toxicities. Doses of 3, 6, and 12 nmol of TcapQ488 were delivered intravitreally to normal healthy NHP eyes and eyes that had undergone hemiretinal endodiathermy axotomy (HEA) in the inferior retina. Post-injection fundus fluorescence imaging using a Spectralis imaging platform (Heidelberg Engineering) documented TcapQ488 activation in RGC cell bodies. Optical coherence tomography (OCT), slit-lamp examinations, intraocular pressure measurements, and visual electrophysiology testing were performed to monitor probe tolerability. For comparison, a negative control, non-cleavable, non-quenched probe (dTcap488, 6 nmol), was delivered intravitreally to a normal healthy eye. In normal healthy eyes, intravitreal injection of 3 nmol of TcapQ488 was well-tolerated, while 12 nmol of TcapQ488 to the healthy eye caused extensive probe activation in the ganglion cell layer (GCL) and eventual retinal nerve fiber layer thinning. In HEA eyes, the HEA procedure followed by intravitreal TcapQ488 (3 nmol) injection resulted in probe activation within cell bodies in the GCL, confined to the HEA-treated inferior retina, indicating cell injury and slow axonal transport in the GCL. However, in contrast to rodents, a vitreal haze that lasted 2-12 weeks obscured rapid high-resolution imaging of the fundus. By contrast, intravitreal TcapQ488 injection prior to the HEA procedure led to minimal probe labeling in the GCL. The results of the dTcap488 control experiments indicated that fast axonal transport carried the probe out of the retina after cell body uptake. No evidence of pan-retinal toxicity or loss of retino-cortical function was detected in any of the three NHPs tested. Overall, these data provide evidence of TcapQ488 activation, without toxicity, in NHP HEA eyes that had been intravitreally injected with 3 nmol of the probe. Compared to rodents, unexpectedly rapid axonal transport in the NHPs reduced the capacity to visualize RGC cell bodies and axons through the backdrop of an intravitreal haze. Nonetheless, although intravitreal clearance rates did not scale to NHPs, HEA-induced reductions in axonal transport enhanced probe visualization in the cell body.